Putusan Pengadilan Negeri Dobo Terhadap Tindak Pidana Pemilu - Patiasina, Pieter H; Wadjo, Hadibah Zachra; Elia Rumangun, Johan Pieter (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
In its development, general election crimes in Indonesia have experienced many changes, both in the form of increasing types of criminal acts and differences in the addition of criminal sanctions. This is because every day, election crimes are becoming a very serious concern because the measure of a democratic country's success is seen from its success in holding elections. The aim of this research is to examine and analyze the basic considerations of Dobo District Court judges in imposing fines on perpetrators of criminal acts, and the Dobo District Court Decision Number 60/Pid.Sus/2020/PN.Dob can have a deterrent effect on defendants who commit election crimes. This type of research is normative juridical in nature. The research type is descriptive-analytical. Sources of legal materials use primary legal materials and secondary legal materials. Techniques for collecting legal materials through literature study and qualitative analysis of legal materials. The research results show that the basis for the judge's consideration in imposing a fine in court decision Number 60/Pid.Sus/2020/PN Dob is because the judge considers both juridical and non-juridical considerations. Juridically, the defendant's actions could harm other people, while non-juridically, the defendant was cooperative and polite, thereby making the trial run smoothly and the defendant has never been punished. all of which cannot be separated from the indictments and demands filed by the public prosecutor with a single charge of election crimes. And in the decision of the Dobo District Court Number 60/Pid.Sus/2020/PN.Dob it does not have a deterrent effect on defendants who commit election crimes because fines can only be felt by poor people, but in essence these fines do not applies to the perpetrator in this case because the perpetrator of the election crime is the Chairman of the Aru Islands Regency DPRD who of course is economically capable of carrying out a fine, therefore the fine expected in this decision does not have a deterrent effect.